Klasifikasi SD Unggulan dalam Pengembangan Infrastruktur Pendidikan di Kupang Timur Menggunakan Naive Bayes Berbasis SIG - Sanchia Aryuasti Maakh; Max ABR. Soleman Lenggu (Jurnal Manajemen Informatika & Teknologi, 2025)
Basic education plays an important role in shaping the character and competencies of the young generation, including in East Kupang District, Kupang Regency, East Nusa Tenggara. However, the development of educational infrastructure in this area still faces various challenges, particularly regarding the equitable quality and accessibility of excellent primary schools. This research aims to utilize Geographic Information Systems (GIS) and the Naive Bayes algorithm classification technique to classify elementary schools in East Kupang District based on the completeness of facilities, infrastructure, and other supporting aspects. The research results indicate that the majority of schools are classified as exemplary schools, and the evaluation of the model using a confusion matrix shows an accuracy level of 100%. The classification results are then visualized in the form of a digital map through the integration of ArcGIS and Google My Maps, which illustrates the spatial distribution of exemplary and non-exemplary schools. This system can be used as a basis for strategic planning and policy-making in education development that is more targeted.